2019
DOI: 10.1007/s40751-019-00054-3
|View full text |Cite
|
Sign up to set email alerts
|

From Experiences in a Dynamic Environment to Written Narratives on Functions

Abstract: This study focusses on high school students' written discourse about their experiences in a dynamic interactive digital environment in which functions were represented in one dimension, as dynagraphs, that are digital artefacts in which the independent variable can be acted upon and its movement causes the variation of the dependent variable. After the introduction of the notion of Dynamic Interactive Mediators within the theory of Commognition, we analyze and classify students' written productions describing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…A constant function is represented with the independent variable that can be dragged by a direct motion and the other variable standing still. The relations existing between the mathematical properties of a function and the properties of its dynamic representation are many and they are very deep from a mathematical point of view, see, for example, [37]. In terms of the Theory of Semiotic Mediation [24], the artifact, that is constituted by dynamic graphs, embeds a mathematical knowledge and it is linked to artifact signs (signs related to the movement of points on the screen) and mathematical signs (signs related to the functions' properties expressed within a mathematical theory).…”
Section: Results: the Didactical Activitiesmentioning
confidence: 99%
“…A constant function is represented with the independent variable that can be dragged by a direct motion and the other variable standing still. The relations existing between the mathematical properties of a function and the properties of its dynamic representation are many and they are very deep from a mathematical point of view, see, for example, [37]. In terms of the Theory of Semiotic Mediation [24], the artifact, that is constituted by dynamic graphs, embeds a mathematical knowledge and it is linked to artifact signs (signs related to the movement of points on the screen) and mathematical signs (signs related to the functions' properties expressed within a mathematical theory).…”
Section: Results: the Didactical Activitiesmentioning
confidence: 99%
“…This is particularly true for findings from research conducted in the context of low achievement in mathematics. Recently, a few studies focusing on students' learning within technological environments have started adopting Sfard's (2008) discursive approach (e.g., Lisarelli, 2019;Antonini et al, 2020;Ng, 2016;Sinclair & Heyd-Metzuyanim, 2014) that I introduce in the next section. These studies have started to unveil discourse that develops within such environments, especially in the mathematical context of functions.…”
Section: Mathematics As Discourse and Mathematical Objects As Discursmentioning
confidence: 99%
“…This study builds on research that has used the discursive approach to study digital visual mediators-or DIMs, for short-in students' discourse on functions. Ng (2016) has introduced a distinction between static and dynamic mediators, which Lisarelli, Antonini and Baccaglini-Frank (Antonini et al, 2020;Lisarelli, 2019) have further elaborated, reaching the notion of dynamic interactive mediators (DIMs), digital objects constructed within technological environments that can be manipulated and that give immediate feedback based on such manipulations, in the form of dynamic change; and that for experts in mathematics are realizations of mathematical objects (or aspects of them). Antonini et al (2020) have suggested that DIMs can enable forms of discourse about functions that are not yet formal but that contain meaningful narratives that an expert can "translate" into canonical mathematical discourse.…”
Section: Mathematics As Discourse and Mathematical Objects As Discursmentioning
confidence: 99%
See 2 more Smart Citations